Komunikasi Efektif Dalam Keperawatan : Strategi Penggunaan Bahasa Yang Sederhana Edukasi Pasien: Effective Communication in Nursing: Strategies for Using Simple Language for Patient Education - Al Jamiliyati, Nasikhatul Ulla; N.A, Septia Rizqi; Hayunnisa , Rizky; Eka , Salsabila; Farihatul, Sintia; Rochma, Siti; Sofia (Yayasan Sagita Akademia Maju, 2025)
This article discusses the importance of effective communication in nursing, especially the use of simple language in patient education. Effective communication, using language that is easy to understand, increases patient satisfaction, reduces anxiety, and increases adherence to treatment. Literature studies show that clear and empathetic communication reduces the risk of medical errors, increases patient participation in care decision making, and results in better care outcomes. This article suggests effective communication strategies such as active listening and the use of visual aids to achieve optimal results. In conclusion, effective communication using simple language is the key to quality and holistic patient care.